EXPLORING EFL ASSESSMENT IN TURKEY: CURRICULUM AND TEACHER PRACTICES - Çimen, Şeyda Selen (International Online Journal of Education and Teaching, 2022)
This study focuses on the assessment practices of EFL teachers in the upper secondary level in Turkey and explores how teachers’ assessment practices and the assessment dimension of English language curriculum (for grades 9 – 12) match. In the study, teachers’ purposes of assessing learners, which aspects of language they assess, and how they carry out assessment are examined by comparing the findings to the recommended assessment practices in the curriculum. Additionally, how EFL teachers feel themselves in their assessment practices is explored. The study employs qualitative design by using document analysis, an open-ended questionnaire, and semi-structured interview. The participants are teachers of English who work at upper secondary schools in Turkey. The findings of the study reveal that (1) some of the teacher practices match with the assessment dimension of the curriculum while there is a mismatch between some of them; (2) teachers have misconceptions about authentic assessment and there is a lack of use of authentic assessment, (3) teachers are the only feedback providers in the classroom, and (4) teachers are divided into three groups of feelings about assessment practices as positive, negative, and neutral. Keywords: EFL assessment, high school teachers, teacher practices, national curriculum